2020
DOI: 10.18421/tem94-30
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Characteristics of the Interconnections Urging the Construction Enterprises Development and Regions Economic Growth

Abstract: The proposed modelling of the construction sector and its impact on the economic system of Ukraine based on fuzzy logic methods allowed to optimize the value of industry components due to changes in gross regional product. High adaptability of the used models confirms probability to make a choice of the best strategy of development of the state taking into account the construction potential in particular regions in Ukraine. The scientific value of the research lies in the use of dynamic models of the system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…To understand what resource is involved in energy conservation or efficient use of energy, it is necessary to realise how much energy is actually consumed by the community, where the community can save and what measures will be the most effective. It is also reasonable to take into account social, economic, institutional, technological and environmental aspects of community development (Mokiy et. al.…”
Section: Resultsmentioning
confidence: 99%
“…To understand what resource is involved in energy conservation or efficient use of energy, it is necessary to realise how much energy is actually consumed by the community, where the community can save and what measures will be the most effective. It is also reasonable to take into account social, economic, institutional, technological and environmental aspects of community development (Mokiy et. al.…”
Section: Resultsmentioning
confidence: 99%
“…While determining among the factors of ensuring the economic security of the country the importance of investment security, work [8] does not define the relationship between the innovative development of the country and its industrial-technological development. In addition, the importance of investment and innovation activity of the state and its industrial enterprises to increase the level of economic security is confirmed by studies [9,10]. At the same time, while paper [9] determines that the relationship between investments that "... are transformed into innovations and new competitive production...", the authors did not explain what kind of social effect is achieved in the process of such transformations.…”
Section: A Theoretical-applied Model Has Been Built For Analyzing Ind...mentioning
confidence: 98%
“…Enterprises take an important role, because they change the direction of their business under the infl uence of information from the external environment and produce innovations and new technologies (Rudnichenko et al, 2021). For example, Ilyash et al (Ilyash et al, 2020) believe that one of the crucial factors in the growth of investment attractiveness is access to resources for implementing investment projects in the fi eld of innovation, intellectual property, and for creating and introducing advanced technologies, a digital economy. This explains the feasibility of determining the impact of the industry's innovation activities indices on the industrial products' revenue (Ilyash, Dzhadan, & Ostasz, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%